Gastric volvulus with a large bochdalek hernia in an adult successfully treated with emergency endoscopic reduction followed by elective laparoscopic mesh repair: A case study. Issue 4 (26th July 2016) - Nishihara, Yuichi; Kawaguchi, Yoshiki; Urakami, Hidejiro; Seki, Shiko; Ohishi, Takashi; Isobe, Yoh; Matsumoto, Sumio
Abstract: We report a case of gastric volvulus with a large Bochdalek hernia successfully treated with emergency endoscopic reduction followed by elective laparoscopic mesh repair. The patient was a 71‐year‐old woman with no history of trauma. She was referred to our hospital because of nausea and vomiting after eating. Thoracic and abdominal CT showed gastric volvulus and a large Bochdalek hernia. The patient underwent emergency endoscopic reduction and elective laparoscopic surgery. The defect (10 × 12 cm) was reinforced with a Dual Mesh (expanded polytetrafluoroethylene) and fixed to the diaphragm with nonabsorbable sutures. The postoperative course was uneventful, and no complications or recurrence was found at the 2‐year follow‐up. The endoscopic reduction and elective laparoscopic procedure was performed successfully and resulted in significant clinical improvement in this case.